Quercetin Administration Following Hypoxia-Induced Neonatal Brain Damage Attenuates Later-Life Seizure Susceptibility and Anxiety-Related Behavior: Modulating Inflammatory Response - Wu, Yan; Wei, Huiping; Li, Pei; Zhao, Hui; Li, Ruifang; Yang, Feiyun (Frontiers in Pediatrics, 2022)
Background: Neonatal seizures commonly caused by hypoxia could lead to brain injury and cognitive deficits. Quercetin could cross the blood brain barrier and exerts neuroprotective effects in many neurological disease settings. In this study, we aim to investigate the role of quercetin in attenuating cognitive impairment following hypoxia-induced neonatal seizure (HINS). Method: Sprague-Dawley rats at P7 were exposed to a premixed gas in a hypoxic chamber to induce brain injury, and then continuously administered with quercetin for 21 days. Pentylenetetrazol kindling was used to induce seizures in the evolution. After the hypoxic lesion was stablished, anxiety-related behavior of rats after HINS was assessed using open field test. Memory impairment of rats after HINS was evaluated using novel object-recognition test and elevated plus maze test. The serum and hippocampal concentrations of TNF-a, iNOS, IL-6 MCP-1, and IL-1β were measured using ELISA. The mRNA expression levels of TNF-a, iNOS, IL-6 in the hippocampus were determined using qRT-PCR. The protein levels of TLR4, NF-κB p65, and p-NF-κB p65 in the hippocampus were determined using Western blot. Results: Quercetin administration significantly reduced later-life seizure susceptibility, anxiety-related behavior, and memory impairments in the rats following the HINS when compared to the HINS group without treatment. Both serum and hippocampal proinflammatory cytokines levels were significantly elevated in the rat after HINS. TLR4 protein expressions were increased in the HINS group when compared to control group, and decreased in the group of quercetin. The protein level of p-NF-κB p65 was significantly lower in the quercetin group compared to the HINS group. Conclusion: We demonstrated that Quercetin significantly reduced susceptibility to later-life seizures. Quercetin could downregulate inflammatory response through TLR4/ NF-κB pathway, thereby attenuating HINS-induced anxiety, hippocampal memory impairment, and cognitive impairment in later life following HINS.